Electrical Transport and Magnetic Properties of High-Quality SrxBi2Se3 Single Crystals Obtained by Annealing. Issue 1 (1st August 2022) - Matsumae, T; Pyon, S; Tamegai, T
Abstract: Topological insulator Bi2 Se3 becomes topological superconductors by doping Cu or Sr. These materials attract much interest because of the nematic state showing two-fold symmetry when the magnetic field is applied parallel to ab-plane. In this study, single crystals of Sr x Bi2 Se3 (0.1 ≤ x ≤ 0.3) were grown by the self-flux method followed by annealing process, which improved superconducting properties. Using these high-quality samples, in-plane magnetic-field-angle dependence of resistivity was measured. The result showed two-fold symmetry and indicated the existence of nematic domains. In addition, magnetoresistance as a function of in-plane field direction was measured and is discussed with regard to crystal inhomogeneity. These results help us to perform future experiments of direct visualization of nematic domains.